The importance of neurology and genetic testing in the patient with non-cleft velopharyngeal dysfunction. (July 2021) - John, Hannah Eliza; Koutsoulieri, Leda; Shaw, Adam; Lin, Jean-Pierre; Rahman, Shakeel; Ferguson, Louisa; Timoney, Norma; Atherton, Duncan
Abstract: Objective: A significant proportion of the referrals made to a speech investigation clinic in a cleft unit include patients with non-cleft velopharyngeal dysfunction (VPD). This study aims to quantify the underlying diagnoses of these patients and describe the investigative pathway and diagnostic information subsequent to presentation in our clinic. Materials and methods: The case notes of 136 consecutive patients with non-cleft VPD who attended our Velopharyngeal Investigation (VPI) clinic from July 2014–December 2019 were reviewed. Results: In the paediatric group (n = 118) the most common cause was 22q11 chromosomal anomalies (n = 46), while post palatal tumour resection was the commonest cause of acquired non-cleft VPD in adults (n = 8). Fifty-nine patients were referred to the clinic with a known underlying pathology such as a syndromic diagnosis. Of those presenting without a known aetiology, fifty-eight were referred onto our genetics and/or neurology colleagues. Although a genetic or neurological cause could not be identified in some of those patients, thirty-one patients received a new diagnosis, with subsequent implications for ongoing care. Conclusion: There are a wide range of diagnoses resulting in non-cleft VPD, but there are very few large-scale studies focusing on investigating these patients for an underlying aetiology. This study highlights the role of genetics and neurology in the diagnosis and management plan for this cohort of patients.